ONS SUID-AFRIKAANSE KINDERHELDE - Le Roux, A.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Since Youth Year is celebrated this year it is only suitable that tribute should be paid to the many child heroes that South Africa produced in the past. This article lifts out a few of these young children, describing the particular circumstances of their heroic deeds.